Analisis Perspektif Eclipse of Reason Max Horkheimer terhadap Fenomena Echo Chamber - Fajar Nur Bahri; Astri Amanda Putri; Fathir Al Fath Harahap (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Social media, initially projected as a democratic discourse space, has instead become trapped in the echo chamber phenomenon, narrowing the intellectual horizons of its users. This research aims to analyze the echo chamber phenomenon on social media through the lens of Max Horkheimer’s critical theory, specifically the concept of the